Environmental wildlife and plant conservation - Trivedi, P. R.; Raj, Gurdeep (New Delhi : Akashdeep Publishing House, 1997)
Human Activities Have Been Drastically Changing The Ecological Balance. Therefore, The Efforts Are Being Made On Global Level For Environmental Conservation. The Present Book Entitled Environmental Wildlife And Plant Conservation Deals With The Various Efforts That Are Being Made For The Wildlife And Plant Conservation. In Order To Make The Book More Interesting Case Studies Have Been Selected Mainly From Various Countries. This Book, Which Assumes No Previous Knowledge Of The Subject, Is Based On The Methods Which The Editors Have Found Over A Number Of Years Of Teaching. This Book Has Been Written To Meet The Requirements Of A Wild Range Of Readers Including Environmental Students, Engineers, Doctors, Health Technicians, And Agriculture Scientists.
Includes bibliographical references.
Keywords: Environmental wildlife and planet conservaton